ESTUDO COMPARATIVO DA ATIVAÇÃO MECÂNICA POR MOINHOS DE ALTA ENERGIA E CARACTERIZAÇÃO DOS PRODUTOS OBTIDOS DURANTE REAÇÃO DE REDUÇÃO DO ÓXIDO DE CROMO POR ALUMÍNIO - Castro, Mauricio de (2015)
This study aims to compare the supply capacity of power each of the three main types of high-energy mills: The "SPEX", Planetary and "Attritor" mills. The system used was chromium oxide with metallic aluminum, both are powders. The reduction reaction of chromium oxide with aluminum in the milling does not occur instantaneously, but is stimulated with mechanical activation of the reagents. The mechanical activation in milling, together with the subsequent heat treatment is that makes a reaction. The energy comparison was made between the mill in two steps: In the first step the milling power was varied for the three mills to be able to identify the milling resulted in the highest exotermic energy peak in the reaction, whereas in the second stage ranged -if the time for milling time find themselves exhibited higher energy released in the reaction. This comparison between the reaction energy peaks confirmed the SPEX as the mill with greater power supply capacity, ie: The mill with the largest peak energy released, followed by the Planetary mill and finally by Attritor mill. In the energy comparison, we studied the influence of the presence of a process control agent in the reaction energy peaks at different milling powers. The milled samples had their power surges reaction determined by thermal analysis of the post. This energy released in the process varied, tending to exhibit a higher peak energy for each of the evaluated parameters (milling power and milling time). There was the use of x-ray diffraction to show the reduction of ground and treated material. Some samples of the powders were pressed only ground and heat treated in an oven. In order to observe the structures formed in the scanning electron microscope, and correlate the structures formed by reactive process studied. Obtained structures consisting of chromium beads dispersed among a substrate of aluminum oxide, both products of the reduction reaction.